IL-27 promotes Treg cell expression of CD122 and fitness at homeostasis - Zachary R. Lanzar; Daniel L. Aldridge; Elisa Cruz-Morales; Christian A. Howard; Isabella O. Conway; Zhe Zhong; Julia N. Eberhard; Joseph A. Pereira; Anthony T. Phan; Aaron M. Ring; Melissa Parker; Chryssa Kanellopoulou; et al. (Proceedings of the National Academy of Sciences, 2025)
Regulatory T (Treg) cells express high levels of the IL-27R, and in the setting of infection and autoimmunity, the cytokine IL-27 promotes Treg cell activities that mitigate tissue pathology. However, IL-27 appears dispensable for Treg cell development and maintenance as lineage-specific depletion of the IL-27R on Treg cells does not impact these populations at steady state. In contrast, when mice were generated in which the Treg compartment comprised a mix of IL-27R-sufficient and -deficient Treg cells, those that lacked IL-27R were at a competitive disadvantage. Aging experiments illustrate that IL-27R-deficient Treg cells are preferentially eroded, and this defect was associated with reduced expression of CD122, the β chain of the IL-2/15R. Moreover, blockade of CD122 led to a similar loss of Treg cells, and in vitro and in vivo studies highlight that IL-27 promotes Treg cell expression of CD122 and improves responsiveness to IL-2/15. These datasets reveal that homeostatic IL-27 signals provide a competitive advantage that shapes the composition of the Treg cell pool by modulating responsiveness to growth factors.